2004
DOI: 10.1103/physreva.70.013802
|View full text |Cite
|
Sign up to set email alerts
|

Correlated imaging, quantum and classical

Abstract: We analytically show that it is possible to perform coherent imaging by using the classical correlation of two beams obtained by splitting incoherent thermal radiation. A formal analogy is demonstrated between two such classically correlated beams and two entangled beams produced by parametric down-conversion. Because of this analogy, the classical beams can mimic qualitatively all the imaging properties of the entangled beams, even in ways which up to now were not believed possible. A key feature is that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
242
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(246 citation statements)
references
References 24 publications
4
242
0
Order By: Relevance
“…This is why biphoton sources yield background-free ghost images [2,5,6], despite SPDC being a broadband process.…”
Section: Image Contrastmentioning
confidence: 99%
See 1 more Smart Citation
“…This is why biphoton sources yield background-free ghost images [2,5,6], despite SPDC being a broadband process.…”
Section: Image Contrastmentioning
confidence: 99%
“…This arrangement yielded a background-free image that was interpreted as a quantum phenomenon, owing to the entanglement of the source photons [2]. However, subsequent experimental * Electronic address: erkmen@mit.edu [3,4] and theoretical [5,6] considerations demonstrated that ghost imaging can be performed with thermalized laser light, utilizing either photon-counting detectors or CCD detector arrays to obtain ghost images, albeit with a background.…”
Section: Introductionmentioning
confidence: 99%
“…Later it was proved that many features obtained in a ghost imaging experiment could also be reproduced with a pseudothermal classical light source [16]. After two decades of intense debate, we now understand that it can be implemented with either quantum or classical sources, albeit with slightly distinct features [16][17][18][19][20][21]. Leaving aside * torresv@chalmers.se the quantum vs classical debate, the ghost appellative actually offers enormous possibilities for optical imaging hitherto not fully exploited.…”
Section: Introductionmentioning
confidence: 99%
“…The results were similar to those with the entangled source, but with half the visibility. It has since been shown that spatial correlations present in radiation produced using thermal and speckle sources may also lead to ghost imaging ( [4][5][6][7][8][9]). …”
Section: Two-photon Ghost Imagingmentioning
confidence: 99%
“…It has been a topic of great interest since its discovery using entangled photon pairs [1]. Initially, it was believed that the entanglement was a necessary ingredient for the effect, but it has since been found that most aspects of ghost imaging can be simulated using spatially-correlated classical light [2,3], including thermal and speckle sources [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%